Daughters of the mountain : women coal miners in central Appalachia - Tallichet, Suzanne E. (Rural studies series of the Rural Sociological Society., 2006)
Much has been written over the years about life in the coal mines of Appalachia. Not surprisingly, attention has focused mainly on the experiences of male miners. In Daughters of the Mountain, Suzanne Tallichet introduces us to a cohort of women miners at a large underground coal mine in southern West Virginia, where women entered the workforce in the late 1970s after mining jobs began opening up for women throughout the Appalachian coalfields. Tallichet's work goes beyond anecdotal evidence to provide complex and penetrating analyses of qualitative data. Based on in-depth interviews with female miners, Tallichet explores several key topics, including social relations among men and women, professional advancement, and union participation. She also explores the ways in which women adapt to mining culture, developing strategies for both resistance and accommodation to an overwhelmingly male-dominated world.